Cannabis use among Norwegian university students: Gender differences, legalization support and use intentions, risk perceptions, and use disorder. (June 2021) - Burdzovic Andreas, Jasmina; Sivertsen, Børge; Lønning, Kari Jussie; Skogen, Jens Christoffer
Highlights: Past year cannabis use was fairly common in a sample of Norwegian college students. About 6% of users possibly met criteria for use disorder, function of use frequency. Legalization attitudes and risk perceptions were associated with cannabis use risk. Intentions to use cannabis if legal were evident even among some current non-users. Many non-users expressed uncertainty in legalization attitudes and risk perceptions. Abstract: Aims: We explored past-year cannabis use and associated characteristics, focusing on legalization attitudes, use intentions, risk perceptions, and possible dependence among Norwegian university/college students. Methods: We examined a nation-wide sample of Norwegian university/college students (N = 49, 688; 67% female) who participated in the Students' Health and Wellbeing Study (SHoT-study) in 2018. Participants reported past-year substance use, support for cannabis legalization, intent to use cannabis if legal, and perceived risks of weekly use. Past-year cannabis use (including use frequency) was examined in relation to these indicators. Legalization support, use intentions, and risk perceptions were examined in relation to use and gender. Potential cannabis use disorder was assessed with the Cannabis Abuse Screening Test (CAST) and examined in relation to use frequency and gender. Findings: Past-year use was reported by 15.3% (11.8% women; 22.9% men). Majority of current users (roughly 90%) used no more than 50 times past year, and 6% (3.8% women; 8.5% men) met CAST use disorder criteria. Legalization support, use intentions, and no/low risk perceptions were significantly associated with greater odds of use, and greater use frequency among current users in both crude and adjusted models. Legalization support (23.0%), use intentions (14.0%), and perceptions of no/low risk (29.2%) were also relatively common even among current non-users, especially men. Male gender and more frequent use were associated with greater CAST scores and greater odds of use disorder. Conclusions: Cannabis use was relatively common in this student sample. In addition to targeting frequent use, interventions may focus on cannabis-related attitudes and risk perceptions among uncertain/uninformed students.